2020
DOI: 10.1007/s10660-020-09415-2
|View full text |Cite
|
Sign up to set email alerts
|

A multi-perspective lens on web assurance seals: contrasting vendors’ intended and consumers’ perceived effects

Abstract: Web assurance seals are actions taken by e-commerce vendors to increase their trustworthiness and alleviate consumers' concerns. In their essence, web assurance seals are a product of negotiations, adoptions, and settlements among various groups of interests (e.g., seal authorities, vendors, consumers, or governmental institutions). However, previous research has hitherto used a unilateral research perspective when studying web assurance seals (i.e., either consumer-or vendor-centric), which has acted as a gri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 111 publications
(199 reference statements)
1
14
0
Order By: Relevance
“…Indeed, while the central (or core)-periphery dichotomy shares some similarities with other approaches (see notably the cue diagnosticity framework mobilized by Purohit & Srivastava, 2001) one of its main advantages is to provide a specific methodological framework which allows us to distinguish which cues are considered as central and which ones are considered as peripheral (Lo Monaco et al, 2017, Rochira et al, 2020. Moreover, these methodologies rely directly on consumers' perceptions and not on an a priori classification created by experts and which may not accurately reflect one of the former (Löbbers, Lins, Kromat, Benlian, & Sunyaev, 2020). Yet, a direct comparison between the central-periphery dichotomy and the other cue frameworks, notably regarding their ability to predict quality assessment and product choice, is yet to be carried out in order to properly distinguish the strengths and weaknesses of this new approach.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, while the central (or core)-periphery dichotomy shares some similarities with other approaches (see notably the cue diagnosticity framework mobilized by Purohit & Srivastava, 2001) one of its main advantages is to provide a specific methodological framework which allows us to distinguish which cues are considered as central and which ones are considered as peripheral (Lo Monaco et al, 2017, Rochira et al, 2020. Moreover, these methodologies rely directly on consumers' perceptions and not on an a priori classification created by experts and which may not accurately reflect one of the former (Löbbers, Lins, Kromat, Benlian, & Sunyaev, 2020). Yet, a direct comparison between the central-periphery dichotomy and the other cue frameworks, notably regarding their ability to predict quality assessment and product choice, is yet to be carried out in order to properly distinguish the strengths and weaknesses of this new approach.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, certifications are a long established and widely acknowledged thirdparty assessment type, enabling organizations to demonstrate that their IS comply with standards. They reduce uncertainties for users as they can rely on a trusted third-party to attest that the system is safe for use, especially when system features cannot be observed (e.g., system bias) (Löbbers et al, 2020).…”
Section: Ai Assessmentmentioning
confidence: 99%
“…We position our study in this user-centered stream of certification research because we adopt a user perspective to examine users' certification understanding problem and how to design IS certification presentations increasing their effects on users. Extant research's evidence of the positive effects of certifications in increasing users' perceived assurance and trust perceptions remains inconclusive (Table 1; Adam et al, 2020;Löbbers et al, 2020). One group of studies has observed that certifications have a significant positive effect on users' perceived assurance (e.g., K. Kim & Kim, 2011;Yang et al, 2006) and trust perceptions (e.g., Hoffmann et al, 2015;Mavlanova et al, 2016).…”
Section: Related Research On Certificationsmentioning
confidence: 99%
“…Well-known certifications include now among others "Certified Privacy" for webshops, "CSA STAR" for cloud services, and management standards for security "ISO/IEC 27001-Information security management systems". System owners can benefit from presenting well-established and recognized certifications in their websites or system user interfaces because certifications increase users' perceived assurance concerning system use and foster users' trust perceptions toward the system owner (Löbbers et al, 2020). In the context of IS use, system owners typically signal the possession of such certifications by placing assurance seals as certification presentations on their websites or in their system interfaces (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation